2020
DOI: 10.1090/tran/8172
|View full text |Cite
|
Sign up to set email alerts
|

End-point estimates, extrapolation for multilinear Muckenhoupt classes, and applications

Abstract: In this paper we present the results announced in the recent work by the first, second, and fourth authors of the current paper concerning Rubio de Francia extrapolation for the so-called multilinear Muckenhoupt classes. Here we consider the situations where some of the exponents of the Lebesgue spaces appearing in the hypotheses and/or in the conclusion can be possibly infinity. The scheme we follow is similar, but, in doing that, we need to develop a one-variable end-point off-diagonal extrapolation result. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
(90 reference statements)
0
28
0
Order By: Relevance
“…Vector-valued extensions of multilinear Calderón-Zygmund operators have mostly been studied within the more restrictive framework of ℓ p spaces and function lattices. Boundedness of these extensions is classically obtained through weighted norm inequalities, more recently in connection with localized techniques such as sparse domination: see [16] and the more recent [6,37,42] for a non-exhaustive overview of their interplay. The paper [10], by Y. Ou and one of us, contains a bilinear multiplier theorem which applies to certain non-lattice UMD spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector-valued extensions of multilinear Calderón-Zygmund operators have mostly been studied within the more restrictive framework of ℓ p spaces and function lattices. Boundedness of these extensions is classically obtained through weighted norm inequalities, more recently in connection with localized techniques such as sparse domination: see [16] and the more recent [6,37,42] for a non-exhaustive overview of their interplay. The paper [10], by Y. Ou and one of us, contains a bilinear multiplier theorem which applies to certain non-lattice UMD spaces.…”
Section: Introductionmentioning
confidence: 99%
“…We send to Subsection 3.3 and to the references [7,8] for more details on sparse bounds and to [37,38] for a survey of the weighted inequalities that may be derived as a consequence. Theorem 1.3 is obtained as a corollary of Theorem 3.31 using Example 3.21.…”
Section: Introductionmentioning
confidence: 99%
“…For p 3 ≤ 1 it follows from the sparse domination for BHF Π established in Theorem 8.4: this implies weighted estimates which, by extrapolation, yield the claimed bounds (97) (plus further weighted estimates that we do not discuss here). The details of this weighted multilinear extrapolation are worked out in [38,Section 4.1] (see also [29,30]).…”
Section: Bounds For Bht Including Quasi-banach Exponentsmentioning
confidence: 99%
“…From the point of view of weights, it was made clear by Li, Martell, and Ombrosi in [31] that rather than assuming a condition on each individual weight, it is more appropriate to consider the multilinear weight classes characterized by the multisublinear analogue of the Hardy Littlewood maximal operator, introduced by Lerner, Ombrosi, Pérez, Torres, and Trujillo-González in [29]. Subsequently, through the extrapolation theorems of the second author [40] and Li, Martell, Martikainen, Ombrosi, and Vuorinen [30], it was shown that these weight classes allow one to handle vector-valued extensions with Banach function spaces outside of the class of UMD spaces, such as ∞ . However, these methods do not exceed the example of iterated L q -spaces.…”
Section: Introductionmentioning
confidence: 99%